Factors affecting entrepreneurship decision in Los Baños, Laguna, Philippines - Huang, Mark Anthony C.; Camacho, Jose DV Jr.; Depositario, Dinah Pura T.; Bello, Amelia L. (2016)
Entrepreneurship is becoming the popular means to promote economic growth and development in different economies. One fundamental issue though is what factors affect an individual's decision to engage in entrepreneurship. This study aims to determine the factors that affect an individual's decision to become an entrepreneur. One-hundred entrepreneurs and 100 non-entrepreneurs in Los Baños, Laguna were the respondents of the study. Probit regression was used to estimate the probability that an individual would become an entrepreneur with respect to some factors. The analysis reveals that six variables are significant:gender, family size, wealth, having entrepreneur-parents, years of schooling and risk tolerance. Women are found to be more inclined to engage in entrepreneurial activity. On the other hand, as the years of schooling of an individual increase, the probability oh his or her engaging in entrepreneurship decreases. Meanwhile, family size has a direct relationship with the decision to become an entrepreneur. Further, the wealthier an individual is, the more likely that he or she would start a business. Lastly, if any or both of an individual's parents is an entrepreneur as well as if an individual is more risk-tolerant, the more likely it is that he/she would become an entrepreneur. The study recommends that personal entrepreneurial development (PED) trainings, low-interest loans and small business insurance mechanisms should be provided to would - be entrepreneurs.
Keywords: Entrepreneurship; Businesspeople; New business enterprises